Peculiar features of correlation between petrophysical signatures of rocks and distribution of geophysical heterogeneities in the Monchegorsk ore area (Kola Peninsula, northeastern Baltic Shield) - Filatova, V.T. (Geofizicheskiy Zhurnal, 2021)
The current article presents stratified data on physical properties of rocks and ores from the Monchegorsk ore area (Kola region). The constructed petrodensity and petromagnetic maps reflect peculiar features of changes in petrophysical parameters of both Paleoproterozoic intrusive rocks and host rocks at the Archean basement of the area. To assess the complementarity degree of physical properties of the rocks and geophysical fields, we additionally analyzed the structure of geophysical anomalies (Δg, ΔZ) in the study area. It allowed constructing a distribution scheme for geophysical heterogeneity in the area and assessing their nature. The conducted studies showed that nickel-bearing and potentially nickel-bearing intrusions in the Monchegorsk ore area were highly dense, but composed of weakly magnetic rocks. Layering of the gabbro-labradorite massif of the Main Ridge is reflected in petrophysical parameters, i. e. endocontact gabbro and gabbronorite show an increased density and magnetic susceptibility compared to leucocratic gabbro and labradorite in the core of the intrusion. Thus, petrophysical data indicate a general increase in the basicity of the rocks towards the bottom of the intrusion. The discrepancy between intense geophysical anomalies and physical parameters of near-surface rocks of the block adjacent to the gabbro-labradorite massif of the Main Ridge in the southeast was revealed. This fact indicates a layer of dense rocks under the supracrustal basement rocks (a complex of gneisses and amphibolized volcanic-sedimentary rocks) and rocks of the Imandra-Varzuga structure. This layer can be composed of potentially nickel-bearing rocks of the Imandra complex, including intrusions of the clinopyroxene-wehrlite formation series exposed in some areas. According to the configuration pattern of the identified axes of local magnetic anomalies, the Archean blocks are considered isolated areas given the uniform pattern they create, i. e. Belomorian — isometric structures, Kola — linearly extended. Therefore, during transformation of the structural plan in the Paleoproterozoic, the Archean blocks gave differentiated responses to the emerging stress-strain state of the environment and were subject to heterogeneous deformations. The performed work, including integrated results of petrophysical studies with the analysis of the structure of geophysical anomalies in the ore region, is relevant in substantiating a strategy for prospecting for new ore occurrences and patterns of their localization, as well as for developing criteria for predicting industrial ores in the region. At the same time, the studies carried out make it possible to answer questions related to the reconstruction of the geodynamic settings that took place during the formation of the region’s crust.